2019
DOI: 10.20473/bhsj.v2i1.13247
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Clinical and Laboratory Profiles of Patients with Acute Lymphoblastic Leukemia at Dr. Soetomo Hospital Surabaya

Abstract: Introduction: Considering the high number of acute lymphoblastic leukemia (ALL) and it being the type of cancer with the highest fatality rate among the children, this study seeks to determine the epidemiological description of the clinical and laboratory profiles of patients with ALL.Methods: This research used a descriptive study by using medical data record of patients with ALL. The research variables were gender, age, leukemia history of the patient’s family, nutritional status, symptoms and signs, laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In a previous study by Putri et al, from 50 ALL patients, 33 patients (66%) had hemoglobin level of 5 -10 g/dL. 5 Another study by Tarigan et al showed 40 patients (48%) had hemoglobin level <7.0 g/dL. 6 Anemia in ALL caused by loss of bone marrow hematopoietic function due to progressive infiltration of malignant leukemia cells.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In a previous study by Putri et al, from 50 ALL patients, 33 patients (66%) had hemoglobin level of 5 -10 g/dL. 5 Another study by Tarigan et al showed 40 patients (48%) had hemoglobin level <7.0 g/dL. 6 Anemia in ALL caused by loss of bone marrow hematopoietic function due to progressive infiltration of malignant leukemia cells.…”
Section: Resultsmentioning
confidence: 98%
“…6 Anemia in ALL caused by loss of bone marrow hematopoietic function due to progressive infiltration of malignant leukemia cells. 5 Leukocyte count in ALL can be found increased, normal, or decreased. 6 In our study, most children and adults showed an increase in leukocyte count (leukocytosis).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations